2011
DOI: 10.1177/0142331211413953
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and control of non-linear variables in a continuous fermentation process using sliding mode techniques

Abstract: Biomass, substrate or metabolite concentrations are difficult to measure online in fermentation processes because of the lack of reliable, cheap and sterilizable transducers. Currently, many of the measurements required may be determined through offline analysis, which is costly and time consuming. Furthermore, the specific growth rate conditions involved in the fermentation are typically non-linear and uncertain. In this paper, a new variable, the substrate consumption rate, consisting of a combination of sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The fermentation process (FP) has a wide range of applications, from the production and storage of food [1] to the production of pharmaceutical products and wastewater treatment. The FP control design is challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation process (FP) has a wide range of applications, from the production and storage of food [1] to the production of pharmaceutical products and wastewater treatment. The FP control design is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The FP control design is challenging. The main obstacle to precise control is the presence of microorganisms [2], as well as the dynamics of FP, which is often incomprehensible, strongly non-linear, and non-stationary [1]. The model parameters vary over a prolonged period due to metabolic variations and physiological modifications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of these key variables is necessary to control and optimize the fermentation process in real-time to enhance the productivity. However, it is hard to measure cell concentration, substrate concentration, product concentration during fermentation process in real-time due to the highly time-varying, non-linear and uncertain nature of the fermentation process 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A SMO was developed to solve the estimation problem by providing a soft sensor to estimate the substrate consumption rate. In addition, it was shown that the observer error dynamics was exponentially stable in Rahman et al (2012). A comparison of observation techniques such as the unscented Kalman filter (UKF), extended Kalman filter (EKF), and a new nonlinear version of SMO were presented for state estimation in Afshar et al (2015).…”
Section: Introductionmentioning
confidence: 99%